2017
DOI: 10.36076/ppj.2017.se52
|View full text |Cite
|
Sign up to set email alerts
|

Oral Oxycodone for Acute Postoperative Pain: A Review of Clinical Trials

Abstract: Background: Opioids are the mainstay of pain management for acute postsurgical pain. Oral oxycodone is an opioid that can provide effective acute postoperative pain relief. Objectives: To evaluate the use of oral oxycodone for acute postoperative pain management. Study Design: This is a narrative review based on published articles searched in PubMed and Medline from 2003 to 2015 on oral oxycodone for acute postoperative pain management. Methods: Clinical trials related to the use of oral oxycodone for acute po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 42 publications
2
36
0
1
Order By: Relevance
“…Doses of sufentanil and sevoflurane influence the level of PONV. In our study, both groups ultimately received equivalent doses and finally nausea or vomitng were similar between groups and with studies already published elsewhere [15,19,27,28].…”
Section: Pacu Periodsupporting
confidence: 89%
See 3 more Smart Citations
“…Doses of sufentanil and sevoflurane influence the level of PONV. In our study, both groups ultimately received equivalent doses and finally nausea or vomitng were similar between groups and with studies already published elsewhere [15,19,27,28].…”
Section: Pacu Periodsupporting
confidence: 89%
“…In conclusion, for clinical purposes, oxycodone or morphine can be used as first-line i. Total dose of study drug (mg) 22 19 [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] 0.048…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that per os oxycodone was associated with better pain control, less serious opioid-related adverse events (ORAEs) and a faster onset of action due to a better pharmacokinetic profile: higher oral bioavailability and lower plasma variability [15][16][17][18][19]. However, controversies have arisen as a result of recent clinical studies and meta-analysis that have shown that per os oxycodone did not reduce adverse events and pain relief.…”
mentioning
confidence: 99%